1984
DOI: 10.1073/pnas.81.15.4912
|View full text |Cite
|
Sign up to set email alerts
|

The heterogeneity and functional capacities of human thymocyte subpopulations.

Abstract: Analysis of human thymocytes with monoclonal antibodies belonging to five distinct clusters of differentiation (CD1, CD3-CD5, CD8) revealed a high degree of phenotypic heterogeneity. Six subpopulations could be defined in the thymic compartment characterized by the presence of CD1 antigens (cortical type); four subpopulations could be defined in the compartment characterized by the lack of CD1 but by the presence of CD5 antigens (medullary type); two subpopulations could be defined in the compartment character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

1985
1985
2000
2000

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 29 publications
(13 reference statements)
0
7
0
Order By: Relevance
“…Depletion with Nal/34 plus complement leaves an enriched population of T3' cells (80-90%) where, surprisingly, T4+ plus T8+ lymphocytes do not account for the whole T3+ subset, suggesting the existence of T3+4-8-thymocytes. Further immunoselection, using OKT4A and B9.4 plus complement, directly shows the existence of a minor (0.5-3%) thymocyte population of T3+4-8-phenotype, not previously described (13,21). In contrast, a phenotypic profile of PBL, using the same procedure shown in Table 1 and elsewhere (13), reveals that T4+ plus T8+ cells account for the whole population of T3+ lymphocytes in peripheral blood.…”
Section: Resultsmentioning
confidence: 50%
See 1 more Smart Citation
“…Depletion with Nal/34 plus complement leaves an enriched population of T3' cells (80-90%) where, surprisingly, T4+ plus T8+ lymphocytes do not account for the whole T3+ subset, suggesting the existence of T3+4-8-thymocytes. Further immunoselection, using OKT4A and B9.4 plus complement, directly shows the existence of a minor (0.5-3%) thymocyte population of T3+4-8-phenotype, not previously described (13,21). In contrast, a phenotypic profile of PBL, using the same procedure shown in Table 1 and elsewhere (13), reveals that T4+ plus T8+ cells account for the whole population of T3+ lymphocytes in peripheral blood.…”
Section: Resultsmentioning
confidence: 50%
“…To characterize the cells responsible for this phenomenon, we performed quantitative flow-cytometric analysis with the T-cell differentiation-cluster mAbs ( Table 1). As previously described (13,21), the thymus comprises a heterogeneous population of T11' lymphocytes, of which about 30% are mature T3' thymocytes and about 70% are immature T6' cells. Depletion with Nal/34 plus complement leaves an enriched population of T3' cells (80-90%) where, surprisingly, T4+ plus T8+ lymphocytes do not account for the whole T3+ subset, suggesting the existence of T3+4-8-thymocytes.…”
Section: Resultsmentioning
confidence: 87%
“…The analysis of the cell surface antigen phenotype has shown that the thymus is composed of a complex and highly heterogeneous population of cells (1,2). The relationship among the different subpopulations and their functional capabilities are still uncertain.…”
mentioning
confidence: 99%
“…The proportion of the thymocyte subpopulation defined by a given phenotype ( Fig. 1) was measured both in immunofluorescence and Cdependent cytotoxicity assays, as previously described [17]. The subpopulations obtained were cultivated for 3 days with ConA and then tested for their suppressive activity after mitomycin treatment.…”
Section: 2mentioning
confidence: 99%